Investigation of Structure and Magnetic Properties of Polycrystalline La0.7Ba0.21Ca0.09Mn1-xNixO3 (x=0.1, 0.2, 0.3) by Sol Gel Method - Prasetyo, P. (Universitas Negeri Yogyakarta, 2020)
Polycrystalline La0,7Ba0,21Ca0,09Mn1-xNixO3 (x = 0,1; 0,2; 0,3) have been synthesized using sol-gel method, the precursors material from pro analysis products. Samples had characterized by XRD, SEM, and VSM. The result of refinement from XRD pattern shown that all materials had single phase with the lattice parameter a and b had decreased with increasing Ni+3 ion and had a rhombohedral structure along with R-3c space group. The materials had nanoparticle distribution particle size based on measurement by SEM. Hysteresis loop shown that the samples La0,7Ba0,21Ca0,09Mn1-xNixO3 (x = 0,1; 0,2; 0,3) are soft magnetic material. Moreover, the increase of Ni+3 ion gave an impact about the magnetization decreasing from the materials which shown by the decreasing of magnetic saturation value.